Study of mid-infrared laser action in chalcogenide rare earth doped glass with Dy3+, Pr3+ and Tb3+ - Sójka, L.; Tang, Z.; Zhu, H.; Bereś-Pawlik, E.; Furniss, D.; Seddon, Angela B.; Benson, Trevor M.; Sujecki, S. (Optical Society of America, 2012)
We present a study of chalcogenide glass fiber lasers doped with Dy3+, Pr3+ or Tb3+ that would operate in the mid-infrared wavelength range. A set of chalcogenide glass samples doped with different concentrations of rare earth ions is fabricated. The modeling parameters are directly extracted from FTIR absorption measurements of the fabricated bulk glass samples using Judd-Ofelt, Füchtbauer–Ladenburg theory and McCumber theory. The modeling results show that, for all the dopants considered, an efficient mid-infrared laser action is possible if optical losses are kept at the level of 1dB/m or below.